Curcumin attenuates BPA-induced insulin resistance in HepG2 cells through suppression of JNK/p38 pathways. (15th April 2017) - Geng, Shanshan; Wang, Shijia; Zhu, Weiwei; Xie, Chunfeng; Li, Xiaoting; Wu, Jieshu; Zhu, Jianyun; Jiang, Ye; Yang, Xue; Li, Yuan; Chen, Yue; Wang, Xiaoqian; et al.
Highlights: BPA induced insulin resistance in HepG2 cells. BPA treatment activated MAPKs pathways in HepG2 cells. Curucumin ameliorated the insulin resistance induced by BPA. Curcumin suppressed BPA-induced JNK/p38 MAPKs in HepG2 cell. Abstract: Bisphenol A (BPA) is an artificial environmental endocrine disrupting chemicals. Accumulating evidence indicates that exposure to BPA contributes to insulin resistance through diverse mechanism including inflammation and oxidative stress. Previous studies have suggested curcumin as a safe phytochemical which can improve obesity-related insulin resistance, inflammation and oxidative stress. The present study aimed to investigate the ability of curcumin to prevent BPA-induced insulin resistance in vitro and the underlying mechanism. Following the establishmet of in vitro insulin resistance via BPA treatment in human liver HepG2 cells, the protective effects of curcumin were determiend. We showed that treatment of HepG2 cells with 100 nM BPA for 5 days induced significantly decreased glucose consumption, impaired insulin signaling, elevation of pro-inflammatory cytokines and oxidative stress, and activation of signaling pathways; inhibition of JNK and p38 pathways, but not ERK nor NF-κB pathways, improved glucose consumption and insulin signaling in BPA-treated HepG2 cells. Moreover, we revealed that curcumin effectively attenuated the spectrum of effects of BPA-triggered insulin resistance, whereas pretreatment with JNK and p38 agonist anisomycin could significantly compensate the effects caused by curcumin. These data illustrated the role of JNK/p38 activation in BPA-induced insulin resistance and suggested curcumin as a promising candidate for the intervention of BPA-induced insulin resistance.